Neuro marketing Role in Individual’s Orientation to Community Participation When Exposing to External Advertising Influences (An Empirical Study) - Afifi, Eman Wadie Abdel Halim (Journal of Economic, Administrative and Legal Sciences, 2020)
This scientific paper refers to the importance of neuro marketing and its feasibility in the marketing process. The response of demographic variables to the research sample for alpha waves represent the state of relaxation and rest, and beta represents the state of thinking and meditation in the brain was studied. It is done when watching an advertisement with eight sections to identify the most important section having the greatest impact on the study sample when watching the advertisement. The conclusion is that both social and psychological factors affect the individual’s behavior towards the community participation, which the study considered as median variables. Impact of some of these ads’ sections differs from the relaxation case (alpha) to meditation (beta). The model of relaxation and rest (alpha) was distinguished from that of meditation and reflection model’s results (beta) in interpreting individual’s behavior towards his community participation. The results of educational level also clearly differed when watching the advertising sections from the other demographic variables (residency- age), which differences were really limited.